"Dear Employer, Let Me Introduce Myself" – Flow, Satisfaction with Work–Life Balance and Millennials' Creativity. Issue 4 (2nd October 2017) - Mihelič, Katarina Katja; Aleksić, Darija
Abstract : With creativity being recognised as a key driver of organizational success, organizations emphasize the need for their employees to be creative and to work long hours. This article takes a step toward understanding the factors contributing to the creativity of millennials, a generation pursuing meaningful work and cherishing a work–life balance. In Study 1 ( n = 238), the relationships between creativity, flow, satisfaction with work–life balance and job crafting were explored; in Study 2 ( n = 120) the focus was on examining flow as the mediator in the relationship between satisfaction with work–life balance and creativity. In experimental Study 3 ( n = 90), the findings from Study 2 were replicated. Overall, the results of the three studies established flow as the mediating variable and demonstrated the beneficial role of satisfaction with the work–life balance and job crafting in the process leading to creativity.